2007
DOI: 10.1080/14034940601181439
|View full text |Cite
|
Sign up to set email alerts
|

Nature and risk factors of injury hospitalization in young adults: A follow-up of 135,987 military conscripts

Abstract: Women were markedly more likely than men to be hospitalized for injury. Moreover, overweight predicted an increased injury risk. Generalizable to the young adult population, the findings should be considered when identifying targets for injury prevention measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 23 publications
0
31
0
Order By: Relevance
“…The relationship between physical fitness and musculoskeletal injuries has been investigated in military conscripts 8 10 31. Heir and Eide8 found that aerobic fitness was associated with injury in univariate analysis, but the relation was no longer significant after adjustment for BMI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationship between physical fitness and musculoskeletal injuries has been investigated in military conscripts 8 10 31. Heir and Eide8 found that aerobic fitness was associated with injury in univariate analysis, but the relation was no longer significant after adjustment for BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Heir and Eide8 found that aerobic fitness was associated with injury in univariate analysis, but the relation was no longer significant after adjustment for BMI. Finnish military conscripts with an excellent aerobic fitness at baseline had a 30% higher injury risk than poor fitness subjects during a 6- to 12-month follow-up (10, table 3). This is in accord with our results, which suggest that the injury absence risk adjusted for confounders was slightly higher in the high than in the lower fitness categories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patients selected for this study comprised of young military trainees who had passed their entry medical examination as healthy and were a�le to perform physically demanding military training. Physical and com�at training includes physical exercise, causing increased loads to the lower lim� and especially to knees �ecause kneeling and crawling are often included in the training activities (15). This training is performed almost daily throughout the service period.…”
Section: Methodsmentioning
confidence: 99%
“…These include, amongst others: female gender [6-9], Caucasian race [10-12], biomechanical factors such as foot structure and flexibility [1,7,11], previous history of injury, high running mileage, high amount of weekly exercise [3,4,13-17], tobacco use [7,11,18,19] and low levels of physical fitness and activity [3,7,10,14,20-24]. The evidence is contradictory, however, with respect to some factors, including age, foot structure, muscular strength and body composition [3,6,7,11,12,21,24,25].…”
Section: Introductionmentioning
confidence: 99%